2003
DOI: 10.1034/j.1399-0039.2003.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fcγ receptor IIb and IIIb polymorphisms with susceptibility to systemic lupus erythematosus in Thais

Abstract: We recently reported association of a newly identified polymorphism of Fcgamma receptor (FcgammaR) IIb, I232T, with systemic lupus erythematosus (SLE) in Japanese. To date, information on FcgammaR genotypes and their association with SLE is limited in South-east Asian populations. To gain further insight into the role of FcgammaR polymorphisms in the genetic predisposition of SLE, association of FcgammaRIIa-H131R, IIb-I232T, IIIa-F176V and IIIb-NA1/NA2 (HNA-1a/1b) polymorphisms with SLE was analyzed in the Tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
127
5
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 152 publications
(141 citation statements)
references
References 55 publications
8
127
5
1
Order By: Relevance
“…Our data support previous findings in 3 other Asian populations (29,32,33). However, the Fc␥RIIb Ile/ Thr187 polymorphism may require epistatic interaction with other genes to express the autoimmune phenotype.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our data support previous findings in 3 other Asian populations (29,32,33). However, the Fc␥RIIb Ile/ Thr187 polymorphism may require epistatic interaction with other genes to express the autoimmune phenotype.…”
Section: Discussionsupporting
confidence: 91%
“…There were significant differences in the genotype distribution between patients with and without pleural effusion ( 2 ϭ 6.59, P ϭ 0.037 by 3 ϫ 2 contingency Strong association of the FCGR2B Ile187Thr polymorphism and SLE in Asian populations. Several published association studies suggest that the FCGR2B minor allele, Thr187, is a risk factor for disease in Thai, Japanese, and Chinese populations, but not in American or Swedish Caucasian or in African American populations (28,29,(32)(33)(34). This differential result does not seem to reflect different population allele frequencies, since the frequencies of the Thr187 allele in these Asian 142 (51) 105 (38) 29 (11) 142 (51) 134 (49) 389 (70) 147 (56) 87 (33) 29 (11) 147 (56) 116 (44) 381 (72) 145 (28) Oral ulcer Positive (n ϭ 112) 59 (53) 42 (38) 11 (10) 0.752 59 (53) 53 (47) 0.853 160 (71) 64 (29) 1.000 Negative (n ϭ 239)…”
Section: Clinical Characteristics Of Sle Patientsmentioning
confidence: 99%
“…Hence, we observed no effects of OPN deletion on CIA, as suggested by Blom et al (8) and in contrast to the findings reported by Yumoto et al (7), using another arthritis model, the CAIA model. There are several conceivable reasons for this contradiction.…”
contrasting
confidence: 56%
“…Moreover, we have demonstrated that expression of OPN is enhanced in arthritic joints of both RA patients (5) and mice with collagen-induced arthritis (CIA) (6). In addition, it has been reported that OPN Ϫ/Ϫ mice are resistant to experimental autoimmune encephalomyelitis (EAE) (3) and to anti-type II collagen (CII) antibody-induced arthritis (CAIA) (7). However, a conflicting report suggests that EAE, CIA, and CAIA are fully inducible without OPN (8), and therefore, the role of OPN in the above inflammatory diseases remains controversial.…”
mentioning
confidence: 99%
See 1 more Smart Citation